1971
DOI: 10.1530/jrf.0.0240219
|View full text |Cite
|
Sign up to set email alerts
|

The Proteins of Bovine Spermatozoa From the Caput and Cauda Epididymidis

Abstract: Summary. Changes occurring in the proteins of bovine spermatozoa during their migration from the caput to the cauda epididymidis were studied.The percentage of total nitrogen in the dry matter was greater in the cauda than in the caput spermatozoa, but the nitrogen content/109 cells was less in the cauda spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 33 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The eluted proteins probably represent species adhering to the outer surface of the membrane. Furthermore, it is possible that the epididymal proteins are related to the new protein bands which appear in epididymal spermatozoa during the course of maturation (Lavon, Volcani & Danon, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The eluted proteins probably represent species adhering to the outer surface of the membrane. Furthermore, it is possible that the epididymal proteins are related to the new protein bands which appear in epididymal spermatozoa during the course of maturation (Lavon, Volcani & Danon, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Epididymal protein changes after epididymal isolation 27 In the present study, DNA and its associated proteins comprised about 50 % of the TEP. Dawson & Scott (1964) and Lavon et al (1971) reported that the DNA content in sperm cells does not change significantly during the maturation process in the epididymal duct. This suggests that the change of DNA and associated protein level in the different portions of the bull epididymis reported here was mainly caused by the differences in the epididymal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The various protein fractions were extracted according to the method described by Lavon, Volcani & Danon (1971); lipoprotein was extracted with OT N-NaOH, acid-soluble protein with OT N-HC1, keratin-like basic protein with OT N-HC1 after treatment with 3 % mercaptoethanol, and the DNA and its associated proteins with 3 % NaOH. Protein levels in each extraction fraction were determined by the Folin reagent method (Lowry, Rosebrough, Farr & Randall, 1951).…”
Section: Methodsmentioning
confidence: 99%
“…Specific protein components are secreted by the epididymis (Lavon, Volcani & Danon, 1971;Killian & Amann, 1973; Koskimies & Kormano, 1975) and the protein composition of epididymal fluid is altered dramatically by castration (Jones & Glover, 1973). However, the role played by epididymal proteins in the development of sperm fertilizing ability is not understood.…”
Section: Introductionmentioning
confidence: 99%